Karakterisasi Struktur Lapisan Tipis Tin Sulfida (SnS) yang Dideposisi dengan Metode Chemical Bath Depotition (CBD) - Al Jalali; M. Anas; Hj. Erniwati (Universitas Halu Oleo, 2017)
Characterization of structural thin tin sulfide (SnS) deposited with a Chemical Bath Depotition (CBD) method has been conducted. The characterization results using X-Ray Difraction (XRD) showed the best results contained in the sample C with a deposition time of 36 hours. SnS diffraction peaks are at 4, 7, 8, 9, 10, and 12 at an angle of 26.9633; 29.8132; 32.9073; 39.3853; 49.5892; and 55.9665 respectively. The value of d (in A) in a row of numbers low peak high peak number is 3.30411; 2.99443; 2.71961; 2.28593; 1.83682; and 1.64168 corresponding to the areas of crystal orthorombik SnS. It denoted as (0 2 1), (0 4 0), (1 3 0), (1 3 1), (1 1 2), and (1 3 2) respectively. Moreover, the values of the lattice parameters: a, b, and c are 4.326 Å; 11.977 Å; and 3.961 Å suggested that that the SnS thin layer has a crystalline structure of orthorombik.